Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1039/d0fo01102a
|View full text |Cite
|
Sign up to set email alerts
|

Soy hull dietary fiber alleviates inflammation in BALB/C mice by modulating the gut microbiota and suppressing the TLR-4/NF-κB signaling pathway

Abstract: Soy hull DF delayed glucose diffusion and absorption of bile acid. Soy hull DF alleviates inflammation in mice through suppressing TLR-4/NF-κB signaling pathway. Soy hull DF ameliorates the colitis induced decrease in gut microbiota species richness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 53 publications
3
20
0
Order By: Relevance
“…Thereby, the SBP may relieve in ammation by increasing the production of anti-in ammatory cytokine IL-10. Likewise, previous studies also found that higher intake of dietary ber was closely related to decreased severity of in ammation, in contrast, dietary ber deprivation resulted in in ammation and increased pathogen susceptibility [43][44][45]. The positive effects of dietary ber on in ammation observed in this study may be correlated to the changed gut microbiota and their by-products induced by the two sources of ber supplementation [46].…”
Section: Discussionsupporting
confidence: 78%
“…Thereby, the SBP may relieve in ammation by increasing the production of anti-in ammatory cytokine IL-10. Likewise, previous studies also found that higher intake of dietary ber was closely related to decreased severity of in ammation, in contrast, dietary ber deprivation resulted in in ammation and increased pathogen susceptibility [43][44][45]. The positive effects of dietary ber on in ammation observed in this study may be correlated to the changed gut microbiota and their by-products induced by the two sources of ber supplementation [46].…”
Section: Discussionsupporting
confidence: 78%
“…Thereby, the SBP may relieve inflammation by increasing the production of antiinflammatory cytokine IL-10. Likewise, previous studies also found that higher intake of dietary fiber was closely related to decreased severity of inflammation, in contrast, dietary fiber deprivation resulted in inflammation and increased pathogen susceptibility [44][45][46]. The positive effects of dietary fiber on inflammation observed in this study may be correlated to the changed gut microbiota and their by-products induced by the two sources of fiber supplementation [47].…”
Section: Discussionsupporting
confidence: 78%
“…Soy milk increases the ratio of Firmicutes and Bacteriodetes due to an increase in Lactobacillus species, and soy milk with fiber greatly decreases the ratio of Allobaculum and Parabacteroides species, related to inflammation in rodents [39]. Soy dietary fiber intake exhibits a positive association with the relative abundance of Lactobacillus, Ruminococcus, Bifidobacteriales, and Flavonifractor at the genus level, which is linked to suppressing tolllike receptor (TLR)-4 → NF-kB signaling pathways in laboratory animals [40,41]. Gut microbiota uses soy dietary fiber as an energy source since it is a soluble dietary fiber.…”
Section: Components Of Soybeans That Function As Prebiotics To Reduce the Risk Of Metabolic Diseases 41 Dietary Fibermentioning
confidence: 99%
“…Isoflavone aglycones can directly reduce intracellular tau-related neurofibrillary tangles and extracellular amyloid-β deposition in the brain, especially the hippocampus, preventing and alleviating neuronal cell death in both in vitro and in vivo studies [20,65]. Dietary fiber and isoflavones in chungkookjang also modulate the gut microbiome to reduce neurotoxin production and elevate neuroprotection components such as butyrate, short-chain fatty acids (SCFA) [4,41]. These components produced by the gut microbiota may also alter systemic inflammation and insulin resistance to influence neuronal cell survival and death by the gut-microbiome-liver-brain axis.…”
Section: Chungkookjang Effects On Systemic and Neuroinflammation And Neuronal Survivalmentioning
confidence: 99%